2018
DOI: 10.1039/c7nj04340f
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted dealkoxycarbonylation of α-mono- and α,α-disubstituted β-keto- and α-cyanoesters mediated by a silica gel bed

Abstract: An alternative microwave-assisted Krapcho-type reaction of α-mono- and α,α-disubstituted β-keto- and α-cyanoesters was efficiently performed on a silica gel bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The carbomethoxy group (−CO 2 Me) of the esters 16a–c was removed by dealkoxycarbonylation using the Krapcho reaction. 13 Whereas the β-ketoesters 16d–j reacted under a novel modification 14 to the aforementioned reaction affording ketones 17d–j (Table 1). Finally, the ester 16k was dealkoxycarbonylated using the Curran method 15 and lithium chloride (entry 11, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbomethoxy group (−CO 2 Me) of the esters 16a–c was removed by dealkoxycarbonylation using the Krapcho reaction. 13 Whereas the β-ketoesters 16d–j reacted under a novel modification 14 to the aforementioned reaction affording ketones 17d–j (Table 1). Finally, the ester 16k was dealkoxycarbonylated using the Curran method 15 and lithium chloride (entry 11, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the product was isolated using a gradient of ethyl ether or ethyl acetate or dichloromethane/hexane mixture. 14…”
Section: Methodsmentioning
confidence: 99%
“…[293] This can be challenging in cases of complex target molecules, as one building block has to be a free thiol 225. was found that Carbimazole 230, the prodrug for Thiamazole (an antithyroid agent to treat hyperthyroidism [294] ), did not give the envisaged cationic sulfide intermediate In line with this observation, heating induced and silica gel-mediated dealkoxycarbonylation reactions of α-monosubstituted β-keto-and α-cyanoesters, have been recently reported by the group of M. Jaramillo-Gómez. [295] Since the unexpected reactivity of imidazole-2-thione 230 gave access to 231, the generality of this methodology was tested with further arenes and heteroarenes as nucleophiles.…”
Section: Investigation Towards a One-step Synthesis Of Imidazolyl Thi...mentioning
confidence: 99%
“…28 -7.36 (m, 3H), 7.73 -7.78 (m, 1H) ppm. 13 Dove et al [295] The solution of 1-methyl-1H-benzimidazole-2-thiol (492 mg, 3.00 mmol, 1.00 equiv.) in dry THF (5 mL) was cooled to 0 °C.…”
Section: Ethyl 2-thioxobenzo[d]oxazole-3(2h)-carboxylate (250)mentioning
confidence: 99%
See 1 more Smart Citation